LECTURERS’ EXPLANATION IN THE STUDENTS EFL CLASSROOM AT MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Rajab, Abd; Rahman, Syarifah Aeni (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2017)
The Students’ attitude toward Lecturers in EFL Classroom at University of Muhammadiyah of Makassar. The objectives of this research were: to find out the students’ attitude toward lecturer’s explanation at the Muhammadiyah University of Makassar. This research was employed descriptive Quantitative. The participants of this research are 40 students in B class and 1 Lecturer at the Muhammadiyah University of Makassar. The result of the research was collected through the use of Questionnaires, and then it was calculated and transcribed to be analyzed. The questionnaire that distributed to 40 students consists of 20 items close-ended and 1 open-ended question. The result showed that the students have good attitudes or not good attitude toward lecturers’ explanation at Muhammadiyah University of Makassar.